Lucerne Meal As An Ingredient In Calf Starter - Geetha A (Department of Animal Nutrition, College of Veterinary and Animal Sciences, 1981)
An investigation was carried out to assess the feeding value of lucerne meal as a possible substitute for fish meal in calf starters. Eighteen cross bred calves, weaned at birth, were divided into three groups (Groups 1, 11 and 111) of six animals each as uniformly as possible in regard to body weight and maintained on three isoproteimic calf starter diets, A, B and C containing 0, 15 and 20 per cent levels respectively of lucerne meal in partial or complete replacement of fish meal. Records of fortnightly body weights and body measurements were maintained throughout the course of the experiment. Haematological studies were carried out at monthly intervals. Digestibility coefficients of nutrients in the three rations were determined by conducting a digestion trial towards the end of the experiment. Though the control diet appeared better in promoting growth in calves, the overall daily gains and feed efficiency were almost similar with all the three dietary treatments clearly indicating that lucerne meal can replace fish meal at the levels used and fairely meet the amino acid requirements of the calves. Gains in body weight showing a positive correlation between body weight and body measurements. The normal and similar values for blood constituents indicated that all the animals maintained normal nutritional status and inclusion of lucerne meal at levels as used in the present study did not exert any deleterious effect on the health of the animals. An overall critical assessment of results clearly indicated that with isoproteimic diets licerne meal can be safely included in calf starters at levels of 15 and 20 per cent in partial or complete replacement of fish meal.